(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2009)
Technological revolution and globalization processes, among others factors, have developed certain changes and effects in people, organizations and society, which manifest an authentic social, cultural and economic revolution. In the business and affairs field, the enterprises compete in an more competitive, global, dynamic, complex and unknown environment, therefore they must attend their most exigent requirements. This new environment entail new business and management models in order to be more competitive, and at the same time, this implies new research demands.